Analisis Pembentukan Endapan pada Transportasi Gas Alam Pengaruh Tekanan, Temperatur, dan pH. - Sari Nurhidayat, Akhlis Rahman; Mediansyah; Sarihidaya Laksana, Nur Akhlis (Infotekmesin, 2024)
Natural gas production areas and processing sites for use in the residential and industrial sectors are separated by a long distance. Contaminants such as H2S and CO2 are present when natural gas is transported. The reaction process that occurs in the pipe walls will experience a reduction in material. A process that occurs repeatedly over a long time will form deposits at the bottom of the pipe. This research investigates the sludge produced by the pigging process every month. The sludge characters are identified using SEM and XRD testing, while the condensate is examined using XRF testing. The XRF results show that the presence of Cl- in the condensate increases the anodic reaction in the corrosion process. Condensate has a pH of 5-6, which will cause corrosion around internal piping. Sludge produces Fe3O4, FeS, and FeCO3. Fe3O4 is more dominant than FeS and FeCO3. More FeS is produced by % mol H2S than by % CO2. Because of the existing FeS, the particles formed are irregular.